Museum samples could help to reconstruct the original distribution of Salmo trutta complex in Italy. Issue 6 (5th April 2017) - Splendiani, A.; Fioravanti, T.; Giovannotti, M.; Olivieri, L.; Ruggeri, P.; Nisi Cerioni, P.; Vanni, S.; Enrichetti, F.; Caputo Barucchi, V.
Abstract : Partial D‐loop sequences of museum specimens of brown trout and marble trout ( Salmo trutta species complex ) collected from Mediterranean rivers in the late 19th century were analysed to help to describe the native distribution of these species. All the individuals studied carried native haplotypes, the geographic distribution of which is consistent with published data. These results indicate that museum specimens from the 19th century could represent an opportunity to get a picture of the original genetic diversity distribution of this species complex.